Proses dan hasil pengkajian pembelajaran berbasis pendidikan karakter pada kursus hotel hospital - Kadek Suranata; I Ketut Dharsana; I Nyoman Ari Surya Dharmawan (Indonesian Institute For Counseling, Education and Therapy, 2022)
This Community Service Program aims to strengthen the implementation of Strengthening Character Education in tourism LKP Training through Lesson study models. There are three main stages implemented in the lesson study program, namely plan, do, and see. Two classes with a total of 21 and 23 students respectively along with two structures at LKP OTC Bali were appointed as models that opened classes in lesson study activities. Through discussions of curriculum studies and lesson plans, hospitality courses are selected in this program. Lesson study activities are carried out in two cycles each for each class and model instructor. The observers of this activity are 65 instructors, OTC management staff throughout Bali as internal observers and academics from Ganesha University of Education as external observers. Data on the instructor’s ability to design, implement and evaluate learning is obtained through guided observation carried out by all observers. Data on the character of religious, discipline, hard work and curiosity of students are measured before the program is implemented and after the program ends. The data were analyzed descriptively and percentage. The results of observations show that there is an increase in the ability of instructors in designing character-based learning activities, implementing KDP, and evaluation abilities in cycle II. Based on the results of measuring the character of religious, discipline, endurance and curiosity of students participating in the course can be found an increase in all the characters aspect between before and after taking the hospitality course that integrates the strengthening of character education.